Síndrome do túnel do carpo em idosos: normatização de parâmetros eletrofisiológicos - Naves, Thiago Guimarães (2009)
Objective: To establish electrophysiologic values for CTS diagnosis in the elderly. Casuistic and methods: thirty healthy volunteers with at least 65 years old were selected. Exclusion criteria were: any sensory symptom, peripheral neuropathy, sistemic diseases, alcohol abuse and wrist fracture. The following parameters were calculated: 1. Median sensory distal latency on the segment wrist - digit II, 14 cm (SDL); 2. Median/radial latency difference on the segment wrist - digit I, 10 cm (MRD); 3. Median/ulnar latency difference on the segment wrist - digit IV, 14 cm (MUD4); 4. Median/ulnar mixed latency difference on the segment palm - wrist, 8 cm (MUPD); 5. Combined sensory index (CSI), calculated as the adding of MRD, MUD4 and MUPD; 6. Mixed median palmar latency (PL), 8 cm; 7. Median/ulnar motor latency difference, lumbrical/interossei, 8 cm (LUMB); 8. Median motor distal latency, pulse-APB, 8 cm (DML). Results: Twenty-one volunteers were female and 9 were male. Mean age was 69.9 (range 65-86). The 97.5th upper normal limits suggested were: SDL 3.80 ms, MRD 0.95 ms, MUD4 0.95 ms, MUPD 0.50 ms, PL 2.45 ms, CSI 2.20 ms and DML 4.30 ms. Conclusions: The reference values for MRD, MUD4, MUDP and CSI in elderly are different from youngers. There are quite less differences for DSL and PL and none at all for DML. The use of these new values in elderly will reduce the number of false positives.